The prognostic value of the CT scan in Primary Intracerebral Haemorrhage - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Ab Rahman, Jamalludin; Abdul Rashid, Mohd Amran; Che Abdullah, Shahrin Tarmizi (2012)
Background: Primary intracerebral hemorrhage (PICH) remains the deadliest and most disabling form of stroke. There is no therapy of proven benefit in improving outcome. Objective: To evaluate the use of the computerized tomography (CT) scans as a predictor of in- hospital survival and neurological recovery after PICH. Methods: A prospective study conducted among PICH patients at a tertiary care level hospital. Their clinical and CT scan findings were correlated with the clinical outcome using modified Rankin scores (mRS) of 0-5 at discharge and during 6 months follow-up. For the assessment of functional status, the mRS was contracted into independent (Grade 0 to 2) and dependent (Grade 3 and above) categories. Results: A total of 160 (93 male and 67 female) eligible patients with age range from 25 to 85 years (mean age 58.30 ± 11.44 years) were evaluated. The overall mortality was 32.5 %. About one third (32.7%) of the deaths occurred within first 24 hours, this rose to 38.5% within first 2 days and 84.6% within one week. The mean Glasgow Coma Scale [GCS] score was significantly higher among survivors. (12.8 ± 0.4 vs. 8.5 ± 0.5, p < 0.001) Lobar ICH was the commonest localization (43.8%), followed by basal ganglia / thalamus (28.1 %) and multilobar (13.1%). The best outcome in terms of survival was for the patients with ICH in basal ganglia / thalamus region (86.7 %), followed by lobar (67.1%). Mean ICH volume was significantly higher among the dead than the survivors (65.60 + 36.6 ml vs. 32.30 + 18.3 ml). Good functional outcome was associated with a hematoma volume of less than 30 ml. At discharge majority of the survivors were functionally dependent 76 (70.4%) and only 32 (29.6%) achieved functional independence. After about 6 months follow-up, 5 patients were lost due to default in treatment and invalid telephone number, 69 (84.1%) were independent and 13 (15.9%) were still dependant. The independent significant predictors of acute in- hospital survival were locations of hematoma and hematoma volume. Conclusions: Outcome and functional status at discharge were well correlated with the initial CT scan findings and therefore CT scan is a useful tool in clinical decision making and prognostication.